LANGUAGE MEANS OF INTERTEXT EXPRESSION IN THE HISTORICAL NOVEL “MALLOWS” BY ROMAN IVANYCHUK - Oksana M. Nazarenko; Olena V. Skalatska (Alfred Nobel University Journal of Philology)
The purpose of the article is to study the linguistic means of expressing the intertext in the Ukrainian historical prose of Roman Ivanychuk “Mallows”. To achieve the goal, the following tasks have been solved: 1) the differences in the implementation of intertextuality in the historical novel and artistic discourse are clarified; 2) the specifics of the linguistic means of expressing intertext at linguo-structural levels are revealed; 3) the intertext is analyzed according to the following criteria: method of contextual explanation (implicit or explicit quotation); reproduction in the text (verbatim or transformed); location (epitextual or intratextual); the functional load of the intertext, the method of passporting and its original source. The orientation of the work requires the use of the following methods: descriptive and the method of observation, with the help of which the specifics and means of realizing the intertext in the historical novel are analyzed; analysis and synthesis – for systematization and generalization of research materials; the method of transformational analysis – to identify formal and semantic changes in the recipient text; the method of linguo-stylistic analysis – for the study of linguistic means of expression in the structure of an artistic text from a functional-aesthetic point of view; the method of stylistic analysis – to determine the stylistics of the intertext and the analysis of various stylistic passages found in the historical novel; the method of contextual-interpretative analysis – to clarify the functional load of the means of implementing intertextuality, in particular for the analysis of content categories of the text; elements of componential analysis – to establish the semantic features of relevant components of historical prose; the method of quantitative calculations – to identify the frequency of use of intertextual elements in the work. The research results demonstrate that the following intertext elements are distinguished in the historical novel: quotations, allusions, cento texts, stylization and intertextual nomination. Linguistic means of expressing intertext are defined as: lexical – words and phrases that help introduce intertext into the author’s work; syntactic – constructions of direct and indirect speech, exclamatory, definite-personal and two-member sentences; grammatical – forms of the 1st person singular pronoun and verb forms of the 1st and 2nd person singular and plural; graphic – design in quotation marks and non-text marker – paragraph indentation. Quotations, in terms of explication in the text, are the most common elements. The functions of quotations and allusions are defined: characterological, dialogic, content-creative, structural- compositional. The types of transformation of quotations are revealed: fragmentation and replacement of one or more lexical components, contamination of different quotations, use of individual components, compositional transformations. Allusions are characterized, which contain only a hint by which we recognize them in the novel and refer the reader to literary works, folklore, and historical events. The specifics of the cento text, saturated with various associations and references to pretexts, which often combine allusions and quotations, are detailed. Stylization as a manifestation of intertext at the level of reproducing the stylistics of another text is substantiated. The author’s deliberate combination of the texts of the following styles: official, epistolary, confessional and administrative-office sub-styles, which were used with a certain stylistic purpose, was traced. The intertextual nomination is considered, which involves the use of iconic proper names of historical persons, names of events and significant historical places. We consider religious names to be precedential because they are associated with a certain literary work or a well-known precedential text.